A Comparative Analysis of Leadership Styles and Performance of Definitive and Acting School Principals in Public Schools of Sukorejo District, Pasuruan Regency - Mokhammad Hermansyah; Ahmad Thohorin; M. Furqon Wahyudi (The Future of Education Journal, 2025)
This study aims to analyze the differences in leadership styles and performance between definitive school principals and Acting (PLT) principals in public schools in Sukorejo District, Pasuruan Regency. The main focus of this research is to identify how the difference in leadership status affects decision-making, management stability, and the effectiveness of school program management. Theoretically, this research is based on transformational and instructional leadership concepts, which are believed to play an essential role in improving the quality of learning and student achievement. Based on the qualitative data analysis obtained from interviews and observations, it was found that definitive school principals have a more stable and consistent leadership style and are more flexible in planning long-term programs. On the other hand, Acting principals face limitations in authority and tenure, which affects their ability to make strategic decisions. These findings indicate that the stability of a definitive principal’s leadership is directly related to successful management and consistent educational outcomes in schools. This research is expected to contribute to a deeper understanding of the differences in principal status and its impact on the effectiveness of school management.